2021
DOI: 10.1021/acsapm.1c00793
|View full text |Cite
|
Sign up to set email alerts
|

Ni Nanoparticle-Immobilized Imine-Linked Microspherical Covalent Organic Polymer for Degradation Studies of Organic Dyes

Abstract: In this work, we have synthesized a covalent organic polymer CPEP that exhibits high thermal and chemical stability, N-rich backbone, and spherical morphology that provide high surface-to-volume ratios for uniform confinement of Ni nanoparticles. Subsequently, the synthesis of the hybrid material Ni@CPEP was validated with various physicochemical characterizations and utilized as a potential catalyst for the degradation of vile organic dyes named Congo red, methylene blue, and methyl orange. The kinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…[40,41] For the degradation process, NaBH 4 was used in excess to enhance the reaction rate. [42,43] Control experiments showed a maximum degradation efficiency of MO and OII was achieved ~13-14 % (Figure S12), whereas ~99 % of dye degradation was achieved within ~1 h using the Co-PCPs. These results suggest that Co-PCPs are efficient catalysts for the reductive degradation of anionic dyes by NaBH 4 at room temperature.…”
Section: Anionic Dye Degradation Studiesmentioning
confidence: 99%
“…[40,41] For the degradation process, NaBH 4 was used in excess to enhance the reaction rate. [42,43] Control experiments showed a maximum degradation efficiency of MO and OII was achieved ~13-14 % (Figure S12), whereas ~99 % of dye degradation was achieved within ~1 h using the Co-PCPs. These results suggest that Co-PCPs are efficient catalysts for the reductive degradation of anionic dyes by NaBH 4 at room temperature.…”
Section: Anionic Dye Degradation Studiesmentioning
confidence: 99%
“…18 Synthesis of Ni@CPEP and its application in catalytic degradation of organic dyes. 144 (Reprinted with permission from 144. Copyright r 2021 American Chemical Society.…”
Section: Metal Immobilized Cops As Heterogeneous Catalystsmentioning
confidence: 99%
“…Recently, in 2021, Deepika et al reported a newly synthesized covalent organic polymer (COP) using a new precursor that was connected with its other units using ethylenediamine as a linker. 144 This newly synthesized polymer was designated as CPEP and attained a very specific spherical morphology. The nitrogen-rich architect with a high surface-to-volume ratio provided the uniform confinement of Ni NP's on the exterior of the CPEP surface and hence Ni@CPEP was obtained (Fig.…”
Section: Application In Catalysismentioning
confidence: 99%
“…Among the aforementioned materials, COPs formed from strong covalent bonds containing hetero atoms such as C, N, O, and S are considered more promising. This is due to their high tunable porosity, low mass density, large surface area, high chemical and thermal stability, and long-term durability. COPs have a wide range of applications in energy storage, gas sensing, gas storage, dye degradation, and catalysis. ,,, Various chemical reactions have been studied for the synthesis of COPs, such as condensation and coupling methods. These methods involve drastic conditions like high temperature, inert atmosphere, and controlled pressure .…”
Section: Introductionmentioning
confidence: 99%